Cathodic corrosion: Part 2. Properties of nanoparticles synthesized by cathodic corrosion - Yanson, A.I.; Yanson, Yu.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We demonstrate how cathodic corrosion in concentrated aqueous solutions enables one to prepare nanoparticles of various metals and metal alloys. Using various characterization methods we show that the composition of nanoparticles remains that of the starting material, and the resulting size distribution remains rather narrow. For the case of platinum we show how the size and possibly even the shape of the nanoparticles can be easily controlled by the parameters of corrosion. Finally, we discuss the advantages of using the nanoparticles prepared by cathodic corrosion for applications in (electro-)catalysis.